2010
DOI: 10.1182/blood-2009-06-225979
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the efficacy of CD20 antibody therapy through the engineering of a new type II anti-CD20 antibody with enhanced direct and immune effector cell–mediated B-cell cytotoxicity

Abstract: CD20 is an important target for the treatment of B-cell malignancies, including non-Hodgkin lymphoma as well as autoimmune disorders. B-cell depletion therapy using monoclonal antibodies against CD20, such as rituximab, has revolutionized the treatment of these disorders, greatly improving overall survival in patients. Here, we report the development of GA101 as the first Fc-engineered, type II humanized IgG1 antibody against CD20. Relative to rituximab, GA101 has increased direct and immune effector cellmedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
793
4
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 795 publications
(837 citation statements)
references
References 37 publications
30
793
4
10
Order By: Relevance
“… 101 Chimeric IgG1     Obinutuzumab/ GA101CD20Reduced (<30%)Coexpression with GnT III and α-ManII in CHO cells (GlycoMAb Technology)Enhanced tumor inhibition of GA101 compared with rituximab in human lymphoma xenograft mouse modelsMossner et al. 102 Humanized IgG1   Enhanced B-cell depletion in spleen and lymph nodes of cynomolgus monkeys over rituximabDalle et al. 131     Enhanced tumor growth inhibition over rituximab in human-transformed follicular lymphoma RL model in SCID mice. RituximabCD20afucosylatedCommercial rituximab treated with endoglycosidase/fucosidase to generate GlcNAc-rituximabEnhanced depletion of huCD20 + B cells in an FcγR-humanized mouse model over original rituximabLi et al.…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%
See 1 more Smart Citation
“… 101 Chimeric IgG1     Obinutuzumab/ GA101CD20Reduced (<30%)Coexpression with GnT III and α-ManII in CHO cells (GlycoMAb Technology)Enhanced tumor inhibition of GA101 compared with rituximab in human lymphoma xenograft mouse modelsMossner et al. 102 Humanized IgG1   Enhanced B-cell depletion in spleen and lymph nodes of cynomolgus monkeys over rituximabDalle et al. 131     Enhanced tumor growth inhibition over rituximab in human-transformed follicular lymphoma RL model in SCID mice. RituximabCD20afucosylatedCommercial rituximab treated with endoglycosidase/fucosidase to generate GlcNAc-rituximabEnhanced depletion of huCD20 + B cells in an FcγR-humanized mouse model over original rituximabLi et al.…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%
“…Reduced fucosylation is achieved through the co-expression of GnT-III and αManII in CHO cells. The antibody demonstrated an enhanced binding affinity for FcγRIIIa and consequently, an increased ADCC activity 102 . Results from Phase1b/2 trials indicated that all patients with CLL experienced rapid and sustained removal of B cells in the peripheral blood.…”
Section: Therapeutic Afucosylated Antibody Drugs Approved For Marketmentioning
confidence: 99%
“…Depending on their ability to redistribute CD20 into lipid rafts and to induce CDC, or to induce cell death and homotypic adhesion, anti-CD20 mAb can be classified as Type I or II CD20 antibodies. Schematically, Type I antibodies (such as rituximab) induce CDC with redistribution of CD20 into lipid rafts, whereas type II mAB (such as the murine antibody tositumomab, or the humanized antibody GA101) are believed to act primarily through the direct induction of nonclassical cell death and exhibit low CDC activity (29).…”
Section: Introductionmentioning
confidence: 99%
“…The dose of 18B12 (30 mg/kg) used here was based on that used in a previous study [23]; the dose-response and timecourse studies were previously done at our laboratory (data not shown).…”
Section: Experimental Groupsmentioning
confidence: 99%
“…Because it has been demonstrated that anti-CD20 treatment eliminates pre-existing B-cell activity in human autoimmunity [21], the purpose of the current proposal has been to evaluate the effects of treatment with glycoengineered anti-CD20 antibody 18B12 in mice subjected to SCI [22], in an attempt to investigate the anti-inflammatory and immunological potential of this anti-CD20 drug. 18B12 has been glycoengineered to make a nonfucosylated Fc region that substantially enhances the ability to attach and recruit effector cells, and hence to an increased antibody-dependent cell-mediated cytotoxicity and antibody-dependent cell phagocytosis compared with nonglycoengineered fully fucosylated antibodies [23,24].…”
Section: Introductionmentioning
confidence: 99%